2013
DOI: 10.1111/jomf.12015
|View full text |Cite
|
Sign up to set email alerts
|

I've Got You Under My Skin: Marital Biography and Biological Risk

Abstract: Social relationships shape adult health in profound ways. This study informs our understanding of this association by investigating how the transitions, timing, and exposures to marriage are associated with types of biological risk presumed to serve as pathways to disease and disability. Drawing on the 2005 – 2006 National Social Health and Aging Project (N = 1,062), the authors evaluated how marital biography was associated with cardiovascular, metabolic, and chronic inflammation risk. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 59 publications
5
43
1
1
Order By: Relevance
“…• Further investigations of biological risks (such as cardiovascular risk) and their associations with family circumstances (such as marital biography or marital quality; e.g., Liu and Waite 2014;McFarland et al 2013) are likely to improve our understanding of the pathways to disease and disability.…”
Section: Discussionmentioning
confidence: 99%
“…• Further investigations of biological risks (such as cardiovascular risk) and their associations with family circumstances (such as marital biography or marital quality; e.g., Liu and Waite 2014;McFarland et al 2013) are likely to improve our understanding of the pathways to disease and disability.…”
Section: Discussionmentioning
confidence: 99%
“…We have assumedthat marital characteristics influence sexual outcomes, but this association could have also run in the opposite direction. Another issue pertaining to selection bias is that mortality and marital duration are likely related as marriage is thought to be protective of health (McFarland, Hayward, & Brown, 2013;Waite & Gallagher, 2000). Those married for the shortest period of time were likely those who experienced divorce, making them less healthy and more likely to have died before being selected into the sample than those who had never experienced divorce.…”
Section: Limitationsmentioning
confidence: 99%
“…As mentioned in chapter 4, a parsimonious explanation of the pattern for men is that, conditional on normative-aged entry to marriage, longer marriage duration acts to protect Hayward & Brown 2013), and is consistent with many of the results, including poorer health among the 'no family formation' group, the 'early divorce with children' group, and the 'disrupted marital history, high fertility' group. It is also consistent with the lack of any significant effects for the 'marriage without children', 'late divorce without children', and 'remarriage -no children from 1 st marriage' groups.…”
Section: Family Life Course Trajectories and Physical Healthsupporting
confidence: 58%
“…In conjunction with the hypothesized effect of marriage duration, this suggests a non-linear relationship, with an 'optimum' time for marriage which does not interfere with educational and labor market participation, but maximizes the health benefits of marriage. Available research tends to support the idea that an early marriage is detrimental to health outcomes (Dupre, Beck & Meadows 2009;Grundy & Holt 2000), however some studies also find that late marriage is protective or report a positive linear relationship between age at marriage and health (Dupre, Beck & Meadows 2009;Hughes & Waite 2009;McFarland, Hayward & Brown 2013). Contradictory evidence has also been found by Henretta (2010, who did not find any significant evidence for a relationship between age at marriage and mortality, and Brockmann and Klein (2004), who found that older age at marriage was positively related to mortality.…”
Section: Marital History and Healthmentioning
confidence: 96%